Quasi-Periodic Pulsations in Solar Flares and the Earth's Ionosphere - HAYES, LAURA (Trinity College Dublin. School of Physics. Discipline of Physics, 2019)
Solar ﬂares are the most powerful and energetic physical phenomena in our solar system, releasing radiation across the whole electromagnetic spectrum with total energies reaching on the order of 10^25 in a matter of minutes. On Earth, the conditions of the terrestrial ionosphere are signiﬁcantly aﬀected by the enhanced radiation of such events. A key observational feature of the emission generated in solar ﬂares is the presence of pronounced pulsations and oscillatory signatures known as quasi-periodic pulsations (QPPs). The presence of such QPPs in solar ﬂare emission places important constraints on the interpretation and understanding of fundamental processes that operate in ﬂares. To date, the characteristics and origins of QPPs remain unclear. In this thesis we aim to further our current understanding of the QPP phenomena, in both solar ﬂaring emissions and the geophysical impacts QPPs have on the Earth’s terrestrial ionosphere. The ﬁrst two investigations in this thesis examine the recently identiﬁed temporal ﬁne structure QPPs that are observed in the soft X-ray emissions from solar ﬂares. We present a multi-wavelength investigation of QPPs observed during both the impulsive and decay phases of an X-class solar ﬂare. Unlike previous investigations, we focus on the QPPs evident in the soft X-ray time derivative, and compare this variability with observations at other wavelengths including hard X-ray and microwave observations. The soft X-ray thermal pulsations are found to follow the structure of the non-thermal emission in the impulsive phase of the ﬂare, but then tend towards longer timescales later in the event. This analysis provides new insights into the prevalence of soft X-ray QPPs in solar ﬂaring emission and highlights that these extended ﬁne structure QPPs can persist during both phases of a solar ﬂare, with a potentially diﬀerent dominant QPP driver in each. Following this, a second investigation into the nature of extended soft X-ray QPPs that is observed to exist throughout an entire large solar eruptive X-class ﬂare is presented. This study focuses on relating the soft X-ray QPPs to the spatial length scales and eruptive dynamics of the ﬂaring event. We ﬁnd that there are two regimes of QPPs, an impulsive regime of shorter periods QPPs (∼65 s) that is associated with the extremely fast CME eruption, and an extended decay phase QPP regime with longer periods QPPs (∼150-160 s) associated with co-existing sunward moving features observed in EUV. We also present the ﬁrst observational evidence of the geoeﬀectiveness of QPPs in solar ﬂares. Through the remote sensing of the Earth’s lower ionosphere using Very Low Frequency (VLF) radio wave measurements, together with X-ray and EUV observations, we report the detection of pulsations in the ionospheric electron density that are synchronized with solar ﬂare QPPs. It is found that over the period of a pulsation (∼20 mins), the electron density can vary by up to an order of magnitude. We use these observations, together with the electron continuity equation, to estimate the eﬀective recombination coeﬃcient of the lower ionosphere during the ﬂaring event. Finally we explore some preliminary avenues of future work that build upon the results of this thesis, and discuss the new and exciting directions for the study of the QPP phenomena.
APPROVED